Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need to show the following result:

$$ \int_{-\infty}^\infty \frac{1}{(1+x^2)^{n+1}}dx\, = \frac{1\cdot 3\cdot\ldots\cdot(2n-1)}{2\cdot 4\cdot\ldots\cdot(2n)}\pi $$

With n=1,2,3,...

This function has a pole at i and -i. I've tried a semicircle in the upperhalf of the plain, but the residue then goes to infinity. I've also tried a rectangle in the upperhalf that stays beneath i, but all 3 sides that do not include the integral we're looking for go to zero because of the R in the denominator.

Anyone with tips?

share|cite|improve this question
What do you mean by "the residue then goes to infinity"? – mrf Aug 7 '12 at 9:00

Integrating over a large semicircle in the upper halfplane works well.

Write $$\frac{1}{(1+z^2)^{n+1}} = \dfrac{\dfrac{1}{(z+i)^{n+1}}}{\quad(z-i)^{n+1}\quad}.$$

Hence, the residue at $z=i$ is the $1/n!$ times the $n$th derivative of $1/(z+i)^{n+1}$ evaluated at $z=i$, i.e. $$ \begin{split} \operatorname{Res}\limits_{z=i} \frac{1}{(1+z^2)^{n+1}} &= \frac{1}{n!}\frac{d^n}{dz^n}\left( \frac{1}{(z+i)^{n+1}} \right)\Bigg|_{z=i} \\ &= \frac{1}{n!}(-1)^n(n+1)(n+2)\cdots(2n)\frac{1}{(2i)^{2n+1}} \\ &=\frac{(n+1)(n+2)\cdots(2n)}{n!\cdot2^{2n}\cdot 2i} \\ &= \frac{n!\cdot(n+1)\cdots(2n)}{(n!)^2\cdot 2^{2n}\cdot 2i} \\ &= \frac{(2n)!}{(2\cdot 4\cdot 6\cdots(2n))^2\cdot 2i} \\ &= \frac{1\cdot3\cdot5\cdots(2n-1)}{2\cdot 4\cdot 6\cdots(2n)\cdot 2i} \\ \end{split} $$ I think you can do the last step yourself.

share|cite|improve this answer
Thanks, that seems conclusive! The last steps I can do myself indeed. I also understand all of the rewriting parts, but how did you get from the rewritten integrand to the first way of writing the residue? Can't seem to reproduce that step. (So this: the residue at z=i is the 1/n! times the nth derivative of 1/(z+i)n+1 evaluated at z=i) – boudewijn Aug 7 '12 at 10:29
Rewriting of the integrand shows that it has a pole of order $n$ at $z=i$. There are several ways to compute the residue of higher order poles, but this is usually the easiest way. See your textbook or… – mrf Aug 7 '12 at 11:57

Substitute $x^2=\dfrac{u}{1-u}$ and $\mathrm{d}x=\dfrac{\mathrm{d}u}{2\,u^{1/2}(1-u)^{3/2}}$ $$ \begin{align} \int_{-\infty}^\infty\frac1{(1+x^2)^{n+1}}\mathrm{d}x &=2\int_0^\infty\frac1{(1+x^2)^{n+1}}\mathrm{d}x\\ &=\int_0^1(1-u)^{n-1/2}u^{-1/2}\mathrm{d}u\\ &=\mathrm{B}(n+1/2,1/2)\\ &=\frac{\Gamma(n+1/2)\Gamma(1/2)}{\Gamma(n+1)}\\ &=\frac{(n-\frac12)(n-\frac32)(n-\frac52)\dots\frac12\Gamma(\frac12)}{n(n-1)(n-2)\dots1}\Gamma(\tfrac12)\\ &=\frac{(2n-1)(2n-3)(2n-5)\dots1}{2n(2n-2)(2n-4)\dots2}\pi \end{align} $$

share|cite|improve this answer

if x=tany, $dx=sec^2ydy$ so y varies from $-\frac{\pi}{2}$ to $\frac{\pi}{2}$

$\int 1 / (1+x^{2})^{n+1}dx = \int \frac{sec^2ydy}{(sec^2y)^{n+1}} dy= \int cos^{2n}y dy = I_{2n}(say)$

Here is how to derive the reduction formula

So, $I_m=\frac{cos^{m-1}xsinx}{m}+\frac{m-1}{m}I_{m-2}$


Now if take definite integral of $I_{2n}$ from $-\frac{\pi}{2}$ to $\frac{\pi}{2}$,

$\int_{-\frac{\pi}{2}}^\frac{\pi}{2} cos^{2n}y dy =[\frac{cos^{2n-1}xsinx}{2n}]_{-\frac{\pi}{2}}^\frac{\pi}{2}+\frac{2n-1}{2n}\int_{-\frac{\pi}{2}}^\frac{\pi}{2} cos^{2n-2}y dy=\frac{2n-1}{2n}\int_{-\frac{\pi}{2}}^\frac{\pi}{2} cos^{2n-2}y dy$ (as the first integral is 0)

$I_2= \int cos^2y dy=\int \frac{1+cos2y}{2} dy=\frac{y}{2}+\frac{sin2y}{2}+C$ where C is the indeterminate constant of indefinite integral.

The definite integral of $I_{2}$ from $-\frac{\pi}{2}$ to $\frac{\pi}{2}$ will be $\pi$

So, the definite integral of $I_{2n}$ from $-\frac{\pi}{2}$ to $\frac{\pi}{2}$ will be $\frac{(2n-1)(2n-3)...3.1}{2n(2n-2)...4.2} \int_{-\frac{\pi}{2}}^\frac{\pi}{2} cos^2y dy$

$=\frac{(2n-1)(2n-3)...3.1}{2n(2n-2)...4.2} \pi$

share|cite|improve this answer

Taking the semicircular contour $$C_R:=\left(\gamma_R:=\{z\in\Bbb C\;:\;|z|=R\,\,,\,Im(z)\geq 0\}\right)\cup [-R,R]\,\,,\,R>1$$
the domain within this path contains one pole of the function, and:

$$f(z)=\frac{1}{(1+z^2)^{n+1}}\Longrightarrow Rez_{z=i}(f)=\frac{1}{n!}\lim_{z\to i}\frac{d^n}{dz^n}\left[(z-i)^{n+1}f(z)\right]=$$ $$=\frac{1}{n!}\lim_{z\to i}\frac{d^n}{dz^n}\left[\frac{1}{(z+i)^{n+1}}\right]=\frac{1}{n!}\lim_{z\to i}\frac{(-1)^n(n+1)(n+2)\cdot\ldots\cdot(2n)}{(z+i)^{2n+1}}=$$ $$=\frac{1}{n!}\frac{(-1)^n(n+1)(n+2)\cdot\ldots\cdot(2n)}{(2i)^{2n+1}}=\frac{1}{n!}\frac{(-1)^n(n+1)(n+2)\cdot\ldots\cdot(2n)}{2^{2n+1}(-1)^ni}=$$ $$=\binom{2n}{n}\frac{1}{2^{2n+1}i}$$

We thus get by Cauchy's Integral Theorem that $$\oint_{C_R} f(z)dz=\binom{2n}{n}\frac{\pi}{2^{2n}}\,\,\,\,\,(**)$$

But on $\,\gamma_R\,$ we have $\,z=Re^{it}\,$ , so $$\left|\int_{\gamma_R}f(z)dz\right|\leq\max_{z\in\gamma_R}\left|\frac{1}{(1+R^2e^{2it})^{n+1}}\right|\pi R\leq\frac{\pi R}{(1-R^2)^{n+1}}\xrightarrow [R\to\infty]{} 0$$

So taking the limit when $\,R\to\infty\,$ in (**) we get $$\binom{2n}{n}\frac{\pi}{2^{2n}}=\lim_{R\to\infty}\oint_{C_R} f(z)dz=\int_{-\infty}^\infty\frac{1}{(1+x^2)^{n+1}}dx$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.